MENYIBAK PENYEBAB KETERLAMBATAN PENYELESAIAN LAPORAN KEUANGAN (Studi Kasus pada BKM Bunul Rejo Kota Malang) - Y. Yuliati; Made Sudarma; Ari Kamayanti (InFestasi, 2015)
The background of this research is the high level of delays to complete the financial report which have an impact on the audit process delays and cycle BKM, cause a problem in acquiring fund’s process from APBN and APBD. To explore the understanding of the actors from his experience directly involved in the financial reporting as well as to uncover the reality behind the making of financial reports, case studies are used as an approach to the paradigm intepretif. The results of the analysis from the main informant’s experience, we find that the main problem of financial report’s delay due to internal and external causes which coming from BKM itself. The three main parties were the source of the cause of the delay, namely the preparers of financial statements, the builder and the users of the financial statements.